Invasive adenocarcinoma arising from uterine adenomyosis involving the rectosigmoid colon. Issue 5 (1st August 2004) - Takeuchi, K.; Yamanaka, Y.; Hamana, S.; Ohara, N.; Maruo, T.
Abstract : We describe a rare case of invasive endometrioid adenocarcinoma arising from uterine adenomyosis involving the rectosigmoid colon. At laparotomy the uterus was densely adherent to the rectosigmoid colon. The final pathologic study of surgical specimens revealed intact endometrium and endometrioid adenocarcinoma scattered diffusely throughout the posterior myometrium with direct invasion into the rectosigmoid colon. There were numerous adenomyotic foci around the carcinoma. This case emphasizes the fact that biopsy findings from a uterus with adenocarcinoma arising from adenomyosis can be false negative. Physicians should keep in mind the possible existence of malignancies arising from adenomyosis when uterine malignancies are clinically suspected but histologic evaluation fails to confirm the diagnosis.